Impact of personal cultural orientations and cultural intelligence on subjective success in self-employment in multi-ethnic societies - Martin Baluku; Julius Fred Kikooma; Edward Bantu; Peter Onderi; Kathleen Otto (Journal of Global Entrepreneurship Research, 2019)
The purpose of this paper is to assess the impact of personal cultural orientation and behavioral aspect of cultural intelligence on subjective success in self-employment in a multi-ethnic context. Based on Sharma (J Acad Mark Sci 38: 787-806, 2010) taxonomy of personal cultural orientations, the paper examines the impact of interdependence and social inequality orientations on subjective success in self-employment (measured in terms of job satisfaction). Self-employed individuals working in multiethnic communities in East Africa (Uganda and Kenya) were compared with their counterparts in Germany operating in a less culturally or ethnically diverse context. Moderated mediation analysis using PROCESS macro model 8 is applied to measure the direct and indirect effects. Interdependence and social inequality cultural orientations were positively related to subjective success in self-employment for the East African sample, but not for the Germany sample. The results revealed that the impact of these cultural orientations on subjective success is mediated by behavioral cultural intelligence. However, these indirect effects vary between Germany and East Africa. Similar to cross-cultural settings, multiethnic business settings involve doing business with people from various ethnic and linguistic backgrounds. This requires the entrepreneur to behave in a manner that demonstrates appreciation and respect of other people's cultures.
Keywords: 650; Behavioral cultural intelligence; Entrepreneurial success; Interdependence; Personal cultural orientations; Self-employment; social competencies